Acknowledgement: for the reviewers of Journal of Patan Academy of Health Sciences (Journal of Patan Academy of Health Sciences, 2020)
We from the editorial team greatly appreciate the reviewers for your time and expertise to the journal’s rigorous editorial process, regardless of whether the papers are finally published or not in the JPAHS- Journal of Patan Academy of Health Sciences. We would like to express our sincere gratitude to all the reviewers for your generous contribution.